AB0762 TREATMENT WITH TOFACITINIB IN REFRACTORY PSORIATIC ARTHRITIS. MULTICENTER STUDY OF CLINICAL PRACTICE. (June 2019) - Martín-Varillas, José Luis; Galindez, Eva; Romero, Esteban Rubio; Sellas-Fernández, Agusti; Gonzalez Benitez, Roberto Daniel; Joven-Ibáñez, Beatriz; Esteban, José Campos; Rusinovich, Olga; Calvo-Río, Vanesa; Ortiz-Sanjuán, Francisco; Ventín-Rodríguez, Clara; Fernández-Dominguez, Luis; et al.
Abstract : Background: Tofacitinib (TOFA) is the first inhibitor of JAK kinases with approval for the treatment of psoriatic arthritis (PsA) in Europe (July 2018) 1 . ToFA has shown efficacy in refractory patients to anti-TNF 2 . Objectives: A) to assess efficacy and safety of TOFA in the first cases in Spain in clinical practice. B) to compare the profile of clinical practice patients with clinical trial. Methods: Study of 41 patients of clinical practice with PsA treated with TOFA in Spain. The diagnosis of PsA was made using CASPAR criteria. Patients who received at least one dose of TOFA were included. Results are expressed as percentage, mean±SD or median [IRQ]. Results: 41 patients (23♀/18♂), mean age of 50.2±10.7 years (table 1 ). Pattern joint involvement was as follows: peripheral (n=25), axial (1) and mixed (15). During the PsA evolution, in addition to arthritis, patients also presented enthesitis (60.9%), nail involvement (39%) and dactylitis (31.7%). Prior TOFA, most patients had received oral prednisone or equivalent (max. 17.9±13.6 mg/d), synthetic immunosuppressants (mean 1.9±0.7) and biological therapy (TB) (3.4±1.9). TB were as follows: etanercept (29), adalimumab (29), infliximab (16), golimumab (13), certolizumab (14), secukinumab (30), ustekinumab (22). Apremilast was used in 10. After a mean follow-up of 12.6±9.1 years after the PsA diagnosis, TOFA was started (5 mg/12 h). 60.9% associated prednisone (9.4±6.1 mg/d). In 17 (41.5%) TOFA was started in combined therapy: methotrexate (9) and leflunomide (8); in the remaining 24, monotherapy was prescribed. In addition to active arthritis patients presented skin involvement (53.6%), enthesitis (26.8%), nail involvement (29.2%) and dactylitis (17.1%). Patients of clinical practice compared with clinical trial have a longer duration of PsA, functional disability (HAQ) and received a higher proportion of corticosteroids and TB (anti-TNF and non-anti-TNF) (table 1 ). After a median follow-up of 4 [3-10.5] months, patients showed prompt improvement in the main variables, both in activity indexes (PASI, DAS28, DAPSA) and laboratory test (table 2 ). Minor side effects were reported in 10 patients (gastrointestinal symptoms), and TOFA was discontinued in 1 due to persistent symptoms. Conclusion: In this preliminary study, first patients of clinical practice in Spain with TOFA in PsA had a longer evolution and received a greater number of TB than those of clinical trial. As in the TOFA clinical trial, it seems effective, rapid and relatively safe in daily clinical practice for refractory PsA. References: [1] https://www.ema.europa.eu/documents/overview/xeljanz-epar-medicine-overview_es.pdf [2] Gladman D. N Engl J Med2017; 377: 1525-36. Disclosure of interests: José Luis Martín-Varillas: None declared, Eva Galindez: None declared, Esteban Rubio Romero: None declared, agusti Sellas-Fernández: None declared, Roberto Daniel Gonzalez Benitez: None declared, Beatriz Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, abbVie, and Janssen, José Campos Esteban: None declared, Olga Rusinovich: None declared, Vanesa Calvo-Río: None declared, Francisco Ortiz-Sanjuán: None declared, Clara Ventín-Rodríguez: None declared, Luis Fernández-Dominguez Speakers bureau: Celgene, Novartis, Janssen, antia Crespo Golmar: None declared, Ximena Elizabeth Larco Rojas: None declared, Manuel Moreno : None declared, alejandro Escudero Contreras: None declared, Emma Beltrán: None declared, Rafael Melero: None declared, Maria jose Moreno: None declared, Enrique Raya: None declared, Beatriz arca: None declared, María-Luisa Peral: None declared, Olga Maiz: None declared, Raul Veroz Gonzalez: None declared, alfonso Corrales: None declared, Natalia Palmou-Fontana: None declared, Belén atienza-Mateo: None declared, J. Loricera: None declared, Miguel a González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: abbvie, MSD, and Roche, Consultant for: abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: abbvie, Pfizer, Roche, Bristol-Myers, Janssen